2002
DOI: 10.4049/jimmunol.169.10.5405
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Edge: Inhibiting Measles Virus Infection but Promoting Reproduction: An Explanation for Splicing and Tissue-Specific Expression of CD46

Abstract: Membrane cofactor protein (MCP; CD46) regulates the complement cascade by inhibiting C3b and C4b deposited on self tissue. This function resides in the complement control protein repeats (CCPs), with CCPs 2–4 essential for regulation. MCP is expressed on the inner acrosomal membrane of human sperm, and Abs to CCP1 inhibit sperm-egg interactions. In somatic tissues, New World monkeys express an alternatively spliced form of MCP lacking CCP1. Although retaining complement-regulatory activity, this form is postul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 29 publications
0
31
0
Order By: Relevance
“…However, several molecularly engineered mice already developed to study the function of complement regulatory proteins, including two mDAF knockout mice (40), and mCd59a-(33) and S-proteindeficient mice (41) did not show any major fertility problem. Several in vitro studies suggested a role for MCP in sperm-egg interaction (42), but the targeted deletion of mouse MCP did not affect their reproductive efficacy (43). Together, these studies illustrate that in mice, DAF, mCd59a, MCP, and S-protein are not individually essential for fetal development/survival or for protecting sperm from complement activation in the male or the female reproductive system.…”
Section: ) C Complement Activity In Mcd59bmentioning
confidence: 71%
“…However, several molecularly engineered mice already developed to study the function of complement regulatory proteins, including two mDAF knockout mice (40), and mCd59a-(33) and S-proteindeficient mice (41) did not show any major fertility problem. Several in vitro studies suggested a role for MCP in sperm-egg interaction (42), but the targeted deletion of mouse MCP did not affect their reproductive efficacy (43). Together, these studies illustrate that in mice, DAF, mCd59a, MCP, and S-protein are not individually essential for fetal development/survival or for protecting sperm from complement activation in the male or the female reproductive system.…”
Section: ) C Complement Activity In Mcd59bmentioning
confidence: 71%
“…However, the loss of this repeat does not affect MCP's complement-regulatory ability (33)(34)(35). Surprisingly, New World monkeys retain expression of CCP1 on spermatozoa (32). This conservation of structure suggests that MCP participates in fertilization, in addition to being a complement regulator.…”
Section: Introductionmentioning
confidence: 99%
“…First, as noted, the retention of CCP1 on spermatozoa of New World monkeys and the Ab inhibition data both suggest that CCP1 might be playing a role in fertilization independent of complement activation (32). Second, in 1993 Anderson et al described a model whereby MCP might be one half of a C3b dimer bridge between the spermatozoa and the egg (29).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…is not through traditional C3b binding, but through an alternative binding domain CCP1 which is selectively expressed in the testes of these animals (Riley et al 2002b). In support of this, CCP1…”
Section: Adhesionmentioning
confidence: 71%